2021
DOI: 10.3389/fpubh.2021.741334
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Health Outcomes Among Long-Term Survivors of Childhood Cancer: A Scoping Review

Abstract: The five-year survival rate of childhood cancer has increased substantially over the past 50 yr; however, racial/ethnic disparities in health outcomes of survival have not been systematically reviewed. This scoping review summarized health disparities between racial/ethnic minorities (specifically non-Hispanic Black and Hispanic) and non-Hispanic White childhood cancer survivors, and elucidated factors that may explain disparities in health outcomes. We used the terms “race”, “ethnicity”, “childhood cancer”, “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Patient and caregiver needs are not adequately addressed during the transition from therapy to survivorship care, particularly in patients from culturally and medically underserved backgrounds [7][8][9]. Hispanic/Latino parents and CCS are more likely to report health disparities due to social and structural determinants of health (SDOH) such as individual and family level socioeconomic status, underinsurance, immigration status, and perceived ethnic/ racial discrimination [10,11]. Additionally, in the broader survivorship research, Hispanics/Latinos have a greater prevalence of unmet supportive care needs and limited access to information [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Patient and caregiver needs are not adequately addressed during the transition from therapy to survivorship care, particularly in patients from culturally and medically underserved backgrounds [7][8][9]. Hispanic/Latino parents and CCS are more likely to report health disparities due to social and structural determinants of health (SDOH) such as individual and family level socioeconomic status, underinsurance, immigration status, and perceived ethnic/ racial discrimination [10,11]. Additionally, in the broader survivorship research, Hispanics/Latinos have a greater prevalence of unmet supportive care needs and limited access to information [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our study identified a racial disparity in surgery utilization in pediatric patients with bone LCH: the non-white patients were less likely to be treated with surgery than the whites. In the United States, the racial disparity, whether or not mediated by patient’s socioeconomic status, is an important factor influencing the care and outcome of various childhood neoplasms [22] , [23] , [24] . Our work suggests that equitable care should be stressed in pediatric patients with osseous LCH as well.…”
Section: Discussionmentioning
confidence: 99%
“…14 Racial and ethnic disparities experienced by cancer survivors are multifactorial and mediated by inequitably distributed social determinants of health such as access to health care, clinical trial enrollment, health literacy, and socioeconomic position. [15][16][17] These factors are downstream manifestations of systemic racism, or the interconnected, cross-institutional systems and structures by which persons belonging to historically marginalized racial and ethnic groups are disadvantaged. 18 Racism is widely recognized as an independent social determinant of health and root cause of racial and ethnic disparities.…”
Section: Introductionmentioning
confidence: 99%